Development of predictive models for egg freshness and shelf-life under different storage temperatures. (7th September 2021) - Quan, Chunli; Xi, Qian; Shi, Xueping; Han, Rongwei; Du, Qijing; Forghani, Fereidoun; Xue, Chuanyun; Zhang, Jiacheng; Wang, Jun
Abstract: The objective of the present study was to develop models for egg freshness and shelf-life predictions for the selected evaluation indicators including egg weight, Haugh unit (HU), and albumen height. Experiments were carried out at different storage temperatures for a total period of 29–32 days. All data were collected and fitted in to Arrhenius equation for egg freshness, while the HU data were applied to a probability model for shelf-life prediction. The results showed that egg weight, albumen height, and HU decreased significantly, while albumen pH increased with the extension of storage time. The higher the storage temperature, the faster the egg quality decreased. In addition, the bias factor, accuracy factor, and the standard error of prediction were selected to verify the developed quality models. Maximum rescaled R -square statistic, the Hosmer–Lemeshow goodness-of-fit statistic, and the receiver operating characteristic curve were used to evaluate the goodness-of-fit of the developed probability model for the shelf-life of eggs, which indicated that the presented predictive models can be used to assess egg freshness and predict shelf-life during different storage temperatures.